Pola Perilaku ASN Pasca Pembentukan Daerah Otonom Provinsi Kalimantan Utara - Akadun (Universitas Terbuka, 2021)
The formation of the newly autonomous region of North Kalimantan has a strategic meaning as the Indonesia-Malaysia border area. There are many problems in the border areas which if left unchecked will cause financial losses and erosion of nationalism. This qualitative-descriptive research with constructivism paradigm uses data collection techniques: interviews, observation, and documentation. Triangulation as a data analysis technique and procedure includes data collection, data reduction, data presentation, and concluding. The formation of the Province of North Kalimantan has brought changes to the behavior patterns of ASN both in consumption patterns, patterns of ASN relations with society, patterns of relations between ASN and political elites, and patterns of ASN work.